2019
DOI: 10.1093/jxb/erz005
|View full text |Cite
|
Sign up to set email alerts
|

Developmental plasticity of Arabidopsis hypocotyl is dependent on exocyst complex function

Abstract: Etiolated hypocotyls of exocyst mutants exhibit a defect in hypocotyl plasticity manifested as ectopic collet-like structure formation, associated with deviations in auxin signaling and starch accumulation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
8
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 15 publications
(9 citation statements)
references
References 38 publications
1
8
0
Order By: Relevance
“…The multiplicity of the plant exocyst complex functions has been well documented. Distinct exocyst variants are involved in auxin transport, root and hypocotyl epidermal cell elongation, cytokinesis, pollen tube growth, seed coat formation, defense against pathogens, xylem differentiation, and leaf trichome development ( Cole et al., 2005 ; Synek et al., 2006 ; Hála et al., 2008 ; Kulich et al., 2015 ; Sekereš et al., 2017 ; Vukašinović et al., 2017 ; Janková Drdová et al., 2019 ). On the subcellular level, exocyst participates in plasma membrane protein recycling, cytokinesis, autophagic targeting to the vacuole, and deposition of cell wall material, especially callose, to the pathogen attack site ( Fendrych et al., 2010 ; Pecenková et al., 2011 ; Drdová et al., 2013 ; Žárský et al., 2013 ; Kulich et al., 2018 ; rev.…”
Section: Introductionmentioning
confidence: 99%
“…The multiplicity of the plant exocyst complex functions has been well documented. Distinct exocyst variants are involved in auxin transport, root and hypocotyl epidermal cell elongation, cytokinesis, pollen tube growth, seed coat formation, defense against pathogens, xylem differentiation, and leaf trichome development ( Cole et al., 2005 ; Synek et al., 2006 ; Hála et al., 2008 ; Kulich et al., 2015 ; Sekereš et al., 2017 ; Vukašinović et al., 2017 ; Janková Drdová et al., 2019 ). On the subcellular level, exocyst participates in plasma membrane protein recycling, cytokinesis, autophagic targeting to the vacuole, and deposition of cell wall material, especially callose, to the pathogen attack site ( Fendrych et al., 2010 ; Pecenková et al., 2011 ; Drdová et al., 2013 ; Žárský et al., 2013 ; Kulich et al., 2018 ; rev.…”
Section: Introductionmentioning
confidence: 99%
“…Phenotypic plasticity usually refers to the adaptability of an individual (or a genotype) to cope with environmental changes by modulating one or multiple phenotypic traits (Arnold et al ., 2019; Fusco and Minelli, 2010). The genetic and environmental impacts on the regulation of gene expression or physiological traits were extensively studied in several plant species and specific tissues or organs (Gruber et al ., 2013; dal Santo et al ., 2016; Dal Santo et al ., 2013; Janková Drdová et al ., 2019; Jong et al ., 2019; Ibañez et al ., 2017). Conversely, little if any information is available on the impact of the environment on the induction or repression of the specialized metabolome, especially in seeds.…”
Section: Discussionmentioning
confidence: 99%
“…The study showed that the members of EXO70A, EXO70C, and EXO70G isoforms are usually linked with the growth and development of plants ( Lai, 2016 ; Synek et al, 2017 ; Du et al, 2018 ). Arabidopsis EXO70A1, the best characterized members of EXO70A isoform, involved in cytokinesis ( Fendrych et al, 2010 ), root hair and cell growth ( Synek et al, 2006 ; Wu et al, 2013 ; Cole et al, 2014 ), pollen–stigma interactions ( Safavian et al, 2015 ), hypocotyl development ( Hala et al, 2008 ; Jankova Drdova et al, 2019 ), and primary and secondary cell wall biogenesis ( Li et al, 2013 ; Oda et al, 2015 ; Vukasinovic et al, 2017 ). Instead, EXO70B, E, F, and H isoforms are often related to plant biotic interactions and defense responses.…”
Section: Discussionmentioning
confidence: 99%